2020
DOI: 10.1088/1757-899x/991/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Essential oils and volatile compounds of Kaffir lime (Citrus hystrix D.C) by hydrodistillation method

Abstract: Kaffir lime (Citrus hystrix D.C.), a member of the Citrus family, is a lemon tree naturally grown in tropical regions of Asia. Kaffir lime contains a specific aroma currently used worldwide as spices and cosmetics. Kaffir lime leaves are a famous spice for many dishes of Thai cuisine. The peel of Kaffir lime collected in the southwest of Vietnam was used for essential oil extraction using the process of hydro-distillation. During extraction, 100 g Kaffir lime peel was input at 1:3 ratio, at 120 °C for 90 min. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, the C. hystrix extract analyzed in the present study was lower in citronellal in comparison to previously published data. Since the samples from previously published studies were collected in Malaysia [28], Vietnam [53], and Thailand [50], differences in chemical composition can be attributed their different geographical origins. Furthermore, in the case of the study conducted by Sato et al [50], steam distillation was used as the extraction method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the C. hystrix extract analyzed in the present study was lower in citronellal in comparison to previously published data. Since the samples from previously published studies were collected in Malaysia [28], Vietnam [53], and Thailand [50], differences in chemical composition can be attributed their different geographical origins. Furthermore, in the case of the study conducted by Sato et al [50], steam distillation was used as the extraction method.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigation of C. hystrix cold-pressed EO is currently not available in the literature, several studies compared cold-pressed and hydrodistilled EOs from more common Citrus species. The most common conclusion was that there is a higher recovery of terpene hydrocarbons in cold-pressed oils, which are compounds responsible for the typical aroma of Citrus oils [53,56]. Therefore, the comparison of cold-pressed C. hystrix EO with other extraction methods is highly encouraged for future research related to chemical composition or bioactivity assessment.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the extraction method depends on the properties of the components desired to be obtained 33 . Essential oil production may differ according to factors such as distillation method and extraction device 34–38 . It is stated that in the production of essential oil from some medicinal and aromatic plants, products with different compositions can be obtained depending on the distillation time 39–45 …”
Section: Introductionmentioning
confidence: 99%
“…33 Essential oil production may differ according to factors such as distillation method and extraction device. [34][35][36][37][38] It is stated that in the production of essential oil from some medicinal and aromatic plants, products with different compositions can be obtained depending on the distillation time. [39][40][41][42][43][44][45] However, no study has been found on the effects of such an application on the composition of essential oil in Citrus oils.…”
mentioning
confidence: 99%
“…is a citrus plant that is native to tropical Asia. This plant is commonly cultivated in tropical regions, especially Southeast Asia (Laos, Indonesia, Malaysia, Thailand, and Vietnam) [ 1 , 2 , 3 ]. The leaves and fruits of this plant are recognized as important ingredients in many traditional foods of Southeast Asia, particularly in Thai food [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%